2021
DOI: 10.1029/2020wr028243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flexible and Rigid Vegetation Induced Shear Layers in Partly Vegetated Channels

Abstract: In a variety of environmental settings, including vegetated channel banks and rivers, and their associated floodplains and riparian areas, vegetation occurs along river margins, partially obstructing the cross-section. In these systems, referred to as partly vegetated channels, the long regions of finite width of emergent vegetation laterally interact with the flow, deeply altering the mean and turbulent flow structure with implications on the conveyance capacity of the channel, the water levels, and the mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 97 publications
3
26
0
Order By: Relevance
“…In analogy to other environmental flows over porous obstructions [33], the presence of an inflection point makes the flow susceptible to Kelvin-Helmholtz (KH) type instabilities and the onset of large-scale vortices [31,34,35]. These vortices dominate the vertical transport of momentum, and by analogy of mass and energy, across the vegetated shear layer [36,37]. The vortex and the consequent shear penetration within the canopy define the exchange zone, i.e.…”
Section: Hydrodynamic Features Of Vegetated Floodplain Flowsmentioning
confidence: 99%
See 3 more Smart Citations
“…In analogy to other environmental flows over porous obstructions [33], the presence of an inflection point makes the flow susceptible to Kelvin-Helmholtz (KH) type instabilities and the onset of large-scale vortices [31,34,35]. These vortices dominate the vertical transport of momentum, and by analogy of mass and energy, across the vegetated shear layer [36,37]. The vortex and the consequent shear penetration within the canopy define the exchange zone, i.e.…”
Section: Hydrodynamic Features Of Vegetated Floodplain Flowsmentioning
confidence: 99%
“…The extent of the exchange zone is a primary determinant of residence time in the obstruction [33,38] and has been found to scale upon the canopy drag length scale ⟨C D a⟩ p −1 . The canopy bulk drag ⟨C D a⟩ p is a key dynamic parameter governing the vegetated shear layer [36,38,39]. Experiments on flow over submerged canopies revealed the presence of a pronounced inflection point in the velocity profile only for sufficiently dense canopies, i.e.…”
Section: Hydrodynamic Features Of Vegetated Floodplain Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of fluid (VOF) method was used to investigate the internal flow characteristics of an air induction nozzle (AIN). Caroppi et al [40] studied the impacts of embedding natural plants in the experimental simulation of flow in partly vegetated channels. They found that the normalized shear penetration was 6-10 times greater than observed for rigid cylinders, resulting in wider zones significantly exchanging momentum with the adjacent open water.…”
Section: Introductionmentioning
confidence: 99%